2012
DOI: 10.1111/j.1601-0825.2012.01950.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of HPV infections with second primary tumors in early‐staged oral cavity cancer

Abstract: There are 30% of the patients with OSCC infected with HPV, with most high-risk types. HPV-18 infection may enhance the susceptibility of second primary tumors. Large scale of validation study will be needed to confirm this result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
0
21
1
Order By: Relevance
“…In this study, we found only four poorly differentiated tumors; one of them overexpressed p16 INK4a protein, and only one case with basaloid appearance. Patients with tumors of the oral cavity have been found to have a high incidence of second primary tumors in the oral cavity, with an incidence ranging from 15 to 37 % [11]. In this study, 13 cases of 125 (10 %) developed a second primary tumor, and this was not significantly associated to p16 INK4a overexpression.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In this study, we found only four poorly differentiated tumors; one of them overexpressed p16 INK4a protein, and only one case with basaloid appearance. Patients with tumors of the oral cavity have been found to have a high incidence of second primary tumors in the oral cavity, with an incidence ranging from 15 to 37 % [11]. In this study, 13 cases of 125 (10 %) developed a second primary tumor, and this was not significantly associated to p16 INK4a overexpression.…”
Section: Discussionmentioning
confidence: 49%
“…In patients with OPSCC, HPV infection was found to be associated with favorable prognosis [11]. However, the role of HPV infection on the survival of OSCC patients remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A recent study suggested that the infection of HPV in early-stage oral SCC enhances the susceptibility of developing secondary malignancy, especially HPV-18. 17 However, other authors reported a lower risk of SPT in HPV-positive oropharyngeal SCC, emphasizing that this fact may be a major contributor to the demonstrated superior survival outcomes among patients with HPV-positive disease. 18 The presence of HPV was detected in the esophageal mucosa of our patient, but the oral lesion was HPV-negative.…”
Section: Discussionmentioning
confidence: 96%
“…Some viruses are capable of setting on oncogenesis (HPV) on their own, while others (EBV, CMV, HSV) simply accelerate an already triggered process. Besides, different genotypes of the same virus can be highly oncogenetic (HPV-16, 18), while others are characterised with low or suspected oncogenetic potential (HPV-6, 11) (1,30,35,37,38).…”
Section: Hpv Ebv Hsv and Oral And Oropharyngeal Cancersmentioning
confidence: 99%